Peran Logistik dalam Pembangunan Ekonomi: Analisis Terhadap Manajemen dan Efesiensi Transportasi - Haloho, Prince Eduardo (Peneliti.net, 2024)
Purpose : The purpose of this journal is to analyze and understand more about how risk management and transportation efficiency can affect economic development. This research aims to provide new insights into strategies that can be implemented to improve logistics efficiency, as well as ways to manage risks that may arise in the distribution process. Method : This research uses the literature study method, in which data is collected through a systematic review of scientific publications, journal articles, industry reports, and official documents relevant to the topic of risk management and transportation efficiency in logistics. Data collection techniques involved searching reputable electronic databases and digital libraries to identify the most relevant and up-to-date sources. Result : Logistics plays a crucial role in the economy by managing the delivery and information of goods. Efficiency in logistics is important for customer satisfaction and competitive advantage. Risk management reduces issues such as delays and damage, while transportation efficiency reduces costs and environmental impact. Solid infrastructure and innovation are vital for sustainable economic growth.